Skip to main content

Schur-geometric convexity of the generalized Gini-Heronian means involving three parameters

  • The Erratum to this article has been published in Journal of Inequalities and Applications 2014 2014:516

Abstract

In this paper, we give a unified generalization of the Gini means and Heronian means. The Schur-geometric convexity of the generalized Gini-Heronian means are investigated. Our result generalizes an earlier result given by Shi et al. (J. Inequal. Appl. 2008:879273, 2008). At the end of the paper, two new inequalities related to the generalized Gini-Heronian means are established to illustrate the applicability of the given result.

MSC:26D15, 26E60, 26A51.

1 Introduction

The Schur convexity of functions relating to special means have been investigated by many mathematicians, a number of results can be found in the monograph of Marshall and Olkin [1]. As a supplement to the Schur convexity of functions, the Schur-geometric convexity of functions was recently studied by Shi and Zhang [24], Zhang and Yang [5] and Chu et al. [6], some related results have been found to have an important application in discovering and proving the inequalities for special means. The purpose of this paper is to investigate the Schur-geometric convexity of functions related to Gini means and Heronian means. Besides, as application, we establish two new inequalities for generalized Gini-Heronian means. Our result generalizes an earlier result given by Shi et al. in [7].

In what follows, we denote the set of real numbers by , the set of nonnegative real numbers by R + , the set of positive real numbers by R + + , and the set of nonpositive real numbers by R .

Let (r,s) R 2 , (x,y) R + + 2 ; the classical Gini means are defined by (see [8])

G(r,s;x,y)= { ( x r + y r x s + y s ) 1 / ( r s ) , r s , exp ( x r ln x + y r ln y x r + y r ) , r = s .

In 2007, Sándor [9] investigated the Schur convexity of G(r,s;x,y) with respect to (r,s), and obtained the following result.

Theorem A For fixed (x,y) R + + 2 and xy, the Gini means G(r,s;x,y) is Schur concave with respect to (r,s) on R + 2 , and G(r,s;x,y) is Schur convex with respect to (r,s) on R 2 .

In the same year, Wang [10] proved the Schur convexity and the Schur-geometric convexity of G(r,s;x,y) with respect to (x,y) on R + + 2 , as follows.

Theorem B The Gini means G(r,s;x,y) is Schur convex with respect to (x,y) on R + + 2 if and only if (r,s){(r,s)|r0,s0,r+s1}, and G(r,s;x,y) is Schur concave with respect to (x,y) on R + + 2 if and only if (r,s){(r,s)|r0,r+s1}{(r,s)|s0,r+s1}.

Theorem C The Gini means G(r,s;x,y) is Schur-geometric convex with respect to (x,y) on R + + 2 if and only if (r,s){(r,s)|r+s0}, and G(r,s;x,y) is Schur-geometric concave with respect to (x,y) on R + + 2 if and only if (r,s){(r,s)|r+s0}.

Some different proofs concerning the Schur convexity of G(r,s;x,y) were given by Shi et al. [11], Chu and Xia [12], respectively.

Xia and Chu [13] presented the necessary and sufficient condition for the Schur-harmonic-convexity of G(r,s;x,y) with respect to (x,y) on R + + 2 .

A further discussion on the Schur-power-convexity of G(r,s;x,y) with respect to (x,y) on R + + 2 was given by Yang [14]. Meanwhile, the necessary and sufficient condition for the Schur-power-convexity of G(r,s;x,y) was obtained.

Let (x,y) R + + 2 ; the classical Heronian means is defined by (see [15])

H e (x,y)= x + x y + y 3 .

In 1999, Mao [16] gave the definition of the dual Heronian means as follows:

H ˜ e (x,y)= x + 4 x y + y 6 .

In 2001, Janous [17] considered a unified generalization of the Heronian means H e (x,y) and dual Heronian means H ˜ e (x,y), and presented the following Heronian-type means with a parameter w:

H w (x,y)= { x + w x y + y w + 2 , 0 w < , x y , w = .

Jia and Cao [18] investigated the exponential generalization of the Heronian means,

H p (x,y)= { ( x p + ( x y ) p / 2 + y p 3 ) 1 / p , p 0 , x y , p = 0 ,

and established some related inequalities. Moreover, the monotonicity and Schur convexity of the Heronian means H p (x,y) were discussed by Li et al. in [19].

Shi et al. [7] discussed the Schur convexity and Schur-geometric convexity of a further generalization of the Heronian means given by

H p , w (x,y)= { ( x p + w ( x y ) p / 2 + y p w + 2 ) 1 / p , p 0 , x y , p = 0 ,

and obtained some significant results, asserted by Theorems D and E below.

Theorem D For fixed (p,w) R 2 ,

  1. (1)

    if (p,w){(p,w)|p2,0w2}, then H p , w (x,y) is Schur convex for (x,y) R + 2 ;

  2. (2)

    if (p,w){(p,w)|p1,w0}{(p,w)|1<p3/2,w1}{(p,w)|3/2<p2,w2}, then H p , w (x,y) is Schur concave for (x,y) R + 2 .

Theorem E For fixed (p,w) R 2 ,

  1. (1)

    if (p,w){(p,w)|p>0,w0}, then H p , w (x,y) is Schur-geometric convex for (x,y) R + + 2 ;

  2. (2)

    if (p,w){(p,w)|p<0,w0}, then H p , w (x,y) is Schur-geometric concave for (x,y) R + + 2 .

As a further investigation of Theorem D, Fu et al. [20] gave the necessary and sufficient condition for the Schur convexity of the generalized Heronian means H p , w (x,y). Yang [21] investigated the Schur-power-convexity of H p , w (x,y) with respect to (x,y) R + + 2 . Mortici [22] studied certain special means relating to convex functions.

In this paper, we shall generalize the Gini means G(r,s;x,y) and the Heronian means H p , w (x,y) in a unified form. For this purpose we define a generalized Gini-Heronian means containing three parameters p, q, and w, as follows:

H p , q , w (x,y)= { ( x p + w ( x y ) p / 2 + y p x q + w ( x y ) q / 2 + y q ) 1 / ( p q ) , p q , exp ( x p ln x + ( w / 2 ) ( x y ) p / 2 ln ( x y ) + y p ln y x p + w ( x y ) p / 2 + y p ) , p = q ,

where (p,q) R 2 , (x,y) R + + 2 .

The Schur-geometric convexity of the generalized Gini-Heronian means will be discussed in Section 3. As applications, several inequalities related to generalized Gini-Heronian means are established in Section 4.

2 Definitions and lemmas

We introduce and establish several definitions and lemmas, which will be used in the proofs of the main results in Sections 3 and 4.

Definition 1 (see [1])

For any x=( x 1 , x 2 ,, x n ),y=( y 1 , y 2 ,, y n ) R n , let x [ 1 ] x [ 2 ] x [ n ] and y [ 1 ] y [ 2 ] y [ n ] denote the components of x and y in decreasing order, respectively.

The n-tuple y is said to majorize x (or x is to be majorized by y), in symbols xy, if

i = 1 k x [ i ] i = 1 k y [ i ]  holdsfor k=1,2,,n1and i = 1 n x i = i = 1 n y i .

Definition 2 (see [23])

For any x=( x 1 , x 2 ,, x n ),y=( y 1 , y 2 ,, y n )Ω (Ω R + + n ), ϕ:ΩR is said to be a Schur-geometric convex function on Ω if (ln x 1 ,ln x 2 ,,ln x n )(ln y 1 ,ln y 2 ,,ln y n ) on Ω implies ϕ(x)ϕ(y), ϕ is said to be a Schur-geometric concave function on Ω if and only if −ϕ is a Schur-geometric convex function.

Definition 3 (see [23])

For any x=( x 1 , x 2 ,, x n ),y=( y 1 , y 2 ,, y n )Ω (Ω R + + n ), Ω is said to be a geometrically convex set if ( x 1 α y 1 β , x 2 α y 2 β ,, x n α y n β )Ω for all x,yΩ, α,β[0,1] with α+β=1.

Lemma 1 (see [23])

Let Ω (Ω R + + n ) be symmetric and have a nonempty interior set Ω o , and let ϕ:ΩR be continuous on Ω and differentiable in Ω o . If ϕ is symmetric on Ω and

( x 1 x 2 ) ( x 1 ϕ x 1 x 2 ϕ x 2 ) 0(0)

holds for any ( x 1 , x 2 ,, x n ) Ω o , then ϕ is a Schur-geometric convex (Schur-geometric concave) function.

Lemma 2 (see [7])

Let ab, u(t)=tb+(1t)a, v(t)=ta+(1t)b, 1/2 t 2 t 1 1 or 0 t 1 t 2 1/2, then

( a + b 2 , a + b 2 ) ( u ( t 2 ) , v ( t 2 ) ) ( u ( t 1 ) , v ( t 1 ) ) (a,b).

Lemma 3 Let p,qR, p>q, λ1, and let

g 1 (λ)=p λ p q λ p / 2 + q / 2 +q λ p / 2 q / 2 p.

Then g 1 (λ)0 for p+q0, and g 1 (λ)0 for p+q0.

Proof Let f 1 (λ)=2 λ 1 ( p / 2 q / 2 ) g 1 (λ), f 2 (λ)= λ 1 q f 1 (λ). Straightforward computation yields

f 1 ( λ ) = 2 p 2 λ p / 2 + q / 2 q ( p + q ) λ q + q ( p q ) , f 1 ( 1 ) = 2 ( p q ) ( p + q ) , f 2 ( λ ) = λ 1 q f 1 ( λ ) = p 2 ( p + q ) λ p / 2 q / 2 q 2 ( p + q ) , f 2 ( 1 ) = ( p q ) ( p + q ) 2 , f 2 ( λ ) = 1 2 p 2 ( p + q ) ( p q ) λ p / 2 q / 2 1 .

Case 1. pq0.

  1. (1)

    If p+q=0, then

    g 1 (λ)=p λ p +p λ p / 2 p / 2 p λ p / 2 + p / 2 p=0.
  2. (2)

    If p+q>0, then from the expressions f 2 (λ), f 2 (1), f 1 (1) above we find that, for λ1,

    f 2 (λ)>0, f 2 (1)>0, f 1 (1)>0.

    We thus conclude that the functions f 2 (λ), f 1 (λ), and g 1 (λ) are increasing for λ[1,+). In fact, for λ1, one has

    f 2 ( λ ) > 0 f 2 ( λ ) > 0 f 1 ( λ ) > 0 f 1 ( λ ) > 0 g 1 ( λ ) > 0 g 1 ( λ ) g 1 ( 1 ) = 0 .
  3. (3)

    If p+q<0, then

    f 2 (λ)<0, f 2 (1)>0, lim λ + f 2 ( λ ) λ p / 2 q / 2 = p 2 (p+q)<0.

According to the above relations and the continuity of f 2 (λ), we deduce that there exists λ 1 (1,+) such that f 2 ( λ 1 )=0, which leads us to f 2 (λ)>0 for λ[1, λ 1 ), and f 2 (λ)<0 for λ( λ 1 ,+).

Thus, we deduce that f 1 (λ) is increasing on [1, λ 1 ) and decreasing on ( λ 1 ,+), and thereby we get

f 1 (λ) f 1 ( λ 1 )for  λ 1 (1,+).

On the other hand, we deduce from f 2 ( λ 1 )=0 that λ 1 p / 2 q / 2 = q 2 / p 2 , thus, we have

f 1 ( λ 1 ) = 2 p 2 λ 1 p / 2 q / 2 λ 1 q q ( p + q ) λ 1 q + q ( p q ) = 2 p 2 q 2 p 2 λ 1 q q ( p + q ) λ 1 q + q ( p q ) = q ( p q ) ( 1 λ 1 q ) < 0 ,

which implies f 1 (λ)<0, i.e., g 1 (λ)<0 for λ[1,+).

We conclude that g 1 (λ) is decreasing on [1,+). It, therefore, follows that g 1 (λ) g 1 (1)0.

Case 2. pq=0.

It is easy to verify that:

  • If p>q=0 (it implies that p+q>0), then g 1 (?)=p( ? p -1)=0.

  • If 0=p>q (it implies that p+q<0), then g 1 (?)=q ? - q / 2 (1- ? q )=0.

  • If 0=p=q (it implies that p+q=0), then g 1 (?)=0.

The proof of Lemma 3 is complete. □

Lemma 4 Let p,qR, p>q, λ1, and let

g 2 (λ)=(pq) λ p + q +(p+q) λ p (p+q) λ q (pq).

Then g 2 (λ)0 for p+q0, and g 2 (λ)0 for p+q0.

Proof Let h(λ)= λ 1 q g 2 (λ). It follows from a simple computation that

h ( λ ) = ( p q ) ( p + q ) λ p + p ( p + q ) λ p q q ( p + q ) , h ( 1 ) = 2 ( p q ) ( p + q ) , h ( λ ) = p ( p q ) ( p + q ) λ p 1 ( 1 + λ q ) .

Case 1. pq0.

  1. (1)

    If p+q=0, then

    g 2 (λ)=(p+p) λ p p +(pp) λ p (pp) λ p (p+p)=0.
  2. (2)

    If p+q>0, then from the hypothesis p>q we find that p>(p+q)/2>0, and then we derive from the expressions h (λ), h(1) that, for λ1,

    h (λ)>0,h(1)>0,

    which shows that h(λ) is increasing on [1,+), so, we have h(λ)h(1)>0 for λ1.

    Thus, we obtain g 2 (λ)>0 for λ1. Now, from the fact that g 2 (λ) is increasing on [1,+), we obtain g 2 (λ) g 2 (1)=0 (λ1).

  3. (3)

    If p+q<0 and p>0, then

    h (λ)0,h(1)<0.

    Note that h(λ) is decreasing on [1,+), we get h(λ)h(1)<0 for λ1, and then we get g 2 (λ)<0 for λ1.

    Finally, in view of the fact that g 2 (λ) is decreasing on [1,+), we deduce g 2 (λ) g 2 (1)=0 (λ1).

  4. (4)

    If p+q<0 and p<0, then

    h (λ)>0,h(1)<0, lim λ + h ( λ ) λ p q =p(p+q)>0.

By the monotonicity and the continuity of h(λ), we find that there exists λ 2 (1,+) such that h( λ 2 )=0, which implies that h(λ)<0 for λ[1, λ 2 ), and h(λ)>0 for λ( λ 2 ,+).

We hereby deduce that g 2 (λ)<0 for λ[1, λ 2 ), and g 2 (λ)>0 for λ( λ 2 ,+). Further, we conclude that g 2 (λ) is decreasing on [1, λ 2 ) and increasing on ( λ 2 ,+).

Therefore, we obtain

g 2 (λ)max { g 2 ( 1 ) , lim λ + g 2 ( λ ) } =max { 0 , ( p q ) } =0.

Case 2. pq=0.

It is easy to verify that:

  • If p>q=0 (it implies that p+q>0), then g 2 (?)=2p( ? p -1)=0.

  • If 0=p>q (it implies that p+q<0), then g 2 (?)=2q(1- ? q )=0.

  • If 0=p=q (it implies that p+q=0), then g 2 (?)=0.

This completes the proof of Lemma 4. □

3 Main result

The main result of this paper is given by Theorem 1 below.

Theorem 1 For fixed (p,q,w) R 3 ,

  1. (1)

    if p+q0 and w0, then the generalized Gini-Heronian means H p , q , w (x,y) are Schur-geometric convex for (x,y) R + + 2 ;

  2. (2)

    if p+q0 and w0, then the generalized Gini-Heronian means H p , q , w (x,y) are Schur-geometric concave for (x,y) R + + 2 .

Proof We consider the following two cases.

Case 1. If p=q, then

H p , q , w (x,y)=exp ( x p ln x + ( w / 2 ) ( x y ) p / 2 ln ( x y ) + y p ln y x p + w ( x y ) p / 2 + y p ) .

Differentiating H p , q , w (x,y) with respect to x and y, respectively, we obtain

H x = H p , q , w ( x , y ) G 1 ( x , y , p , w ) x [ x p + w ( x y ) p / 2 + y p ] 2 , H y = H p , q , w ( x , y ) G 2 ( x , y , p , w ) y [ x p + w ( x y ) p / 2 + y p ] 2 ,

where

G 1 ( x , y , p , w ) = [ p x p ln x + x p + ( p w / 4 ) ( x y ) p / 2 ln ( x y ) + ( w / 2 ) ( x y ) p / 2 ] [ x p + w ( x y ) p / 2 + y p ] G 1 ( x , y , p , w ) = p [ x p ln x + ( w / 2 ) ( x y ) p / 2 ln ( x y ) + y p ln y ] [ x p + ( w / 2 ) ( x y ) p / 2 ] , G 2 ( x , y , p , w ) = [ p y p ln y + y p + ( p w / 4 ) ( x y ) p / 2 ln ( x y ) + ( w / 2 ) ( x y ) p / 2 ] [ x p + w ( x y ) p / 2 + y p ] G 2 ( x , y , p , w ) = p [ x p ln x + ( w / 2 ) ( x y ) p / 2 ln ( x y ) + y p ln y ] [ y p + ( w / 2 ) ( x y ) p / 2 ] .

By calculation, it follows that

Λ:=(xy) ( x H x y H y ) = ( x y ) H p , q , w ( x , y ) F ( x , y , p , w ) [ x p + w ( x y ) p / 2 + y p ] 2 ,

where

F ( x , y , p , w ) = G 1 ( x , y , p , w ) G 2 ( x , y , p , w ) = ( p x p ln x + x p p y p ln y y p ) [ x p + w ( x y ) p / 2 + y p ] p [ x p ln x + ( w / 2 ) ( x y ) p / 2 ln ( x y ) + y p ln y ] ( x p y p ) = ( x y ) p / 2 [ x p y p + ( p / 2 ) ( x p + y p ) ln ( x / y ) ] w + 2 p x p y p ln ( x / y ) + x 2 p y 2 p .

Note that the expression Λ is symmetric in x and y, without loss of generality we assume that xy.

Setting λ=x/y, λ1, we have

F(x,y,p,w)= ( x y ) p / 2 y p [ λ p 1 + ( p / 2 ) ( λ p + 1 ) ln λ ] w+ y 2 p ( 2 p λ p ln λ + λ 2 p 1 ) .

In addition, it is easy to show that

[ λ p 1 + ( p / 2 ) ( λ p + 1 ) ln λ ] w + y 2 p ( 2 p λ p ln λ + λ 2 p 1 ) 0 for  p 0  and  w 0 , [ λ p 1 + ( p / 2 ) ( λ p + 1 ) ln λ ] w + y 2 p ( 2 p λ p ln λ + λ 2 p 1 ) 0 for  p 0  and  w 0 .

This yields

Λ0for p0,w0andΛ0for p0,w0.

Case 2. If pq, then

H p , q , w (x,y)= ( x p + w ( x y ) p / 2 + y p x q + w ( x y ) q / 2 + y q ) 1 / ( p q ) .

Differentiating H p , q , w (x,y) with respect to x and y, respectively, we get

H x = H p , q , w ( x , y ) p q [ p x p 1 + ( p w / 2 ) y ( x y ) ( p / 2 ) 1 x p + w ( x y ) p / 2 + y p q x q 1 + ( q w / 2 ) y ( x y ) ( q / 2 ) 1 x q + w ( x y ) q / 2 + y q ] , H y = H p , q , w ( x , y ) p q [ p y p 1 + ( p w / 2 ) x ( x y ) ( p / 2 ) 1 x p + w ( x y ) p / 2 + y p q y q 1 + ( q w / 2 ) x ( x y ) ( q / 2 ) 1 x q + w ( x y ) q / 2 + y q ] .

Direct calculation gives

Λ : = ( x y ) ( x H x y H y ) = H p , q , w ( x , y ) ( x y ) p q [ p ( x p y p ) x p + w ( x y ) p / 2 + y p q ( x q y q ) x q + w ( x y ) q / 2 + y q ] .

It is obvious that the expression Λ is symmetric with respect to p and q (it is also symmetric with respect to x and y), and without loss of generality we assume that xy and p>q in the following discussion.

Simplifying the expression Λ, we obtain

Λ= H p , q , w ( x , y ) ( x y ) F ( x , y , p , q , w ) ( p q ) ( x p + w ( x y ) p / 2 + y p ) ( x q + w ( x y ) q / 2 + y q ) ,

where

F ( x , y , p , q , w ) = p ( x p y p ) ( x q + w ( x y ) q / 2 + y q ) q ( x q y q ) ( x p + w ( x y ) p / 2 + y p ) = ( p x p + ( q / 2 ) y q / 2 q x q + ( p / 2 ) y p / 2 + q x p / 2 y q + ( p / 2 ) p x q / 2 y p + ( q / 2 ) ) w + ( p q ) x p + q + ( p + q ) x p y q ( p + q ) x q y p ( p q ) y p + q = y p + q [ p ( x / y ) p + ( q / 2 ) q ( x / y ) q + ( p / 2 ) + q ( x / y ) p / 2 p ( x / y ) q / 2 ] w + y p + q [ ( p q ) ( x / y ) p + q + ( p + q ) ( x / y ) p ( p + q ) ( x / y ) q ( p q ) ] .

Setting λ=x/y, λ1, then

F(x,y,p,q,w)= y p + q [ λ q / 2 g 1 ( λ ) w + g 2 ( λ ) ] ,

where

g 1 ( λ ) = p λ p q λ p / 2 + q / 2 + q λ p / 2 q / 2 p , g 2 ( λ ) = ( p q ) λ p + q + ( p + q ) λ p ( p + q ) λ q ( p q ) .

It follows from Lemmas 3 and 4 that

F ( x , y , p , q , w ) 0 for  p + q 0  and  w 0 , F ( x , y , p , q , w ) 0 for  p + q 0  and  w 0 .

This evidently implies that

Λ0for p+q0,w0andΛ0for p+q0,w0.

By using the conclusions obtained in Cases 1 and 2 together with an application of Lemma 1, we are led to the desired results:

H p , q , w (x,y) is Schur-geometric convex on R + + 2 when p+q0 and w0. Furthermore, H p , q , w (x,y) is Schur-geometric concave on R + + 2 when p+q0 and w0.

The proof of Theorem 1 is thus completed. □

Remark 1 The main result of Theorem E would follow as a special case of Theorem 1 (q=0). Namely, the result stated in Theorem 1 is an extension of the result given in [7].

4 An application

As an application of Theorem 1, we establish the following interesting inequalities for generalized Gini-Heronian means.

Theorem 2 Let 0<xy, and let 1/2 t 2 t 1 1 or 0 t 1 t 2 1/2.

If p+q0 and w0, then

H p , q , w ( x y , x y ) H p , q , w ( y t 2 x 1 t 2 , x t 2 y 1 t 2 ) H p , q , w ( y t 1 x 1 t 1 , x t 1 y 1 t 1 ) H p , q , w ( x , y ) .
(4.1)

If p+q0 and w0, then

H p , q , w ( x y , x y ) H p , q , w ( y t 2 x 1 t 2 , x t 2 y 1 t 2 ) H p , q , w ( y t 1 x 1 t 1 , x t 1 y 1 t 1 ) H p , q , w ( x , y ) ,
(4.2)

where H p , q , w (x,y) is given by

H p , q , w (x,y)= { ( x p + w ( x y ) p / 2 + y p x q + w ( x y ) q / 2 + y q ) 1 / ( p q ) , p q , exp ( x p ln x + ( w / 2 ) ( x y ) p / 2 ln ( x y ) + y p ln y x p + w ( x y ) p / 2 + y p ) , p = q .

Proof Using Lemma 2 with a substitution a=lnx, b=lny gives

( ln x + ln y 2 , ln x + ln y 2 ) ( t 2 ln y + ( 1 t 2 ) ln x , t 2 ln x + ( 1 t 2 ) ln y ) ( t 1 ln y + ( 1 t 1 ) ln x , t 1 ln x + ( 1 t 1 ) ln y ) ( ln x , ln y ) ,

which is equivalent to

( ln x y , ln x y ) ( ln ( y t 2 x 1 t 2 ) , ln ( x t 2 y 1 t 2 ) ) ( ln ( y t 1 x 1 t 1 ) , ln ( x t 1 y 1 t 1 ) ) ( ln x , ln y ) .

On the other hand, we derive from Theorem 1 that

H p , q , w (x,y) is Schur-geometric convex for p+q0 and w0, H p , q , w (x,y) is Schur-geometric concave for p+q0 and w0.

Thus, from Definition 2, it follows that

H p , q , w ( x y , x y ) H p , q , w ( y t 2 x 1 t 2 , x t 2 y 1 t 2 ) H p , q , w ( y t 1 x 1 t 1 , x t 1 y 1 t 1 ) H p , q , w ( x , y )

for p+q0 and w0; and that

H p , q , w ( x y , x y ) H p , q , w ( y t 2 x 1 t 2 , x t 2 y 1 t 2 ) H p , q , w ( y t 1 x 1 t 1 , x t 1 y 1 t 1 ) H p , q , w ( x , y )

for p+q0 and w0.

The above-mentioned inequalities are the required inequalities in Theorem 2. This completes the proof of Theorem 2. □

Putting q=0 in Theorem 2 gives the following inequalities.

Theorem 3 Let 0<xy, w0, and let 1/2 t 2 t 1 1 or 0 t 1 t 2 1/2. Then, for p0, we have the inequality

G ( x , y ) H p , w ( y t 2 x 1 t 2 , x t 2 y 1 t 2 ) H p , w ( y t 1 x 1 t 1 , x t 1 y 1 t 1 ) H p , w ( x , y ) .
(4.3)

Furthermore, for p0 we have the inequality

G ( x , y ) H p , w ( y t 2 x 1 t 2 , x t 2 y 1 t 2 ) H p , w ( y t 1 x 1 t 1 , x t 1 y 1 t 1 ) H p , w ( x , y ) ,
(4.4)

where G(x,y)= x y , H p , w (x,y) is given by

H p , w (x,y)= { ( x p + w ( x y ) p / 2 + y p w + 2 ) 1 / p , p 0 , x y , p = 0 .

Remark 2 Inequalities (4.3) and (4.4) were first presented by Shi et al. in [7]. It is obvious that the inequalities given in Theorem 2 provide the generalized versions of these inequalities.

References

  1. 1.

    Marshall AW, Olkin I: Inequalities: Theory of Majorization and Its Applications. Academic Press, New York; 1979.

    Google Scholar 

  2. 2.

    Shi H-N, Zhang J: Some new judgement theorems of Schur geometric and Schur harmonic convexities for a class of symmetric functions. J. Inequal. Appl. 2013., 2013: Article ID 527

    Google Scholar 

  3. 3.

    Shi H-N, Zhang J: Schur-convexity of dual form of some symmetric functions. J. Inequal. Appl. 2013., 2013: Article ID 295

    Google Scholar 

  4. 4.

    Shi H-N, Zhang J: Schur-convexity, Schur geometric and Schur harmonic convexities of dual form of a class symmetric functions. J. Math. Inequal. 2014,8(2):349–358.

    MathSciNet  MATH  Google Scholar 

  5. 5.

    Zhang XM, Yang ZH: Differential criterion of n -dimensional geometrically convex functions. J. Appl. Anal. 2007,13(2):197–208.

    MathSciNet  Article  MATH  Google Scholar 

  6. 6.

    Chu Y, Zhang X-M, Wang GD: The Schur geometrical convexity of the extended mean values. J. Convex Anal. 2008,15(4):707–718.

    MathSciNet  MATH  Google Scholar 

  7. 7.

    Shi H-N, Bencze M, Wu S-H, Li D-M: Schur convexity of generalized Heronian means involving two parameters. J. Inequal. Appl. 2008., 2008: Article ID 879273

    Google Scholar 

  8. 8.

    Gini C: Diuna formula comprensiva delle medie. Metron 1938, 13: 3–22.

    MATH  Google Scholar 

  9. 9.

    Sándor J: The Schur-convexity of Stolarsky and Gini means. Banach J. Math. Anal. 2007,1(2):212–215. 10.15352/bjma/1240336218

    MathSciNet  Article  MATH  Google Scholar 

  10. 10.

    Wang Z-H: The sufficient and necessary condition of the Schur-convexity and Schur-geometric-convexity of the Gini means. J. Beijing Inst. Educ. 2007,2(5):1–3.

    Google Scholar 

  11. 11.

    Shi H-N, Jiang Y-M, Jiang W-D: Schur-convexity and Schur-geometrically concavity of Gini means. Comput. Math. Appl. 2009,57(2):266–274. 10.1016/j.camwa.2008.11.001

    MathSciNet  Article  MATH  Google Scholar 

  12. 12.

    Chu Y-M, Xia W-F: Solution of an open problem for Schur convexity or concavity of the Gini mean values. Sci. China Math. 2009,52(10):2099–2106. 10.1007/s11425-009-0116-5

    MathSciNet  Article  MATH  Google Scholar 

  13. 13.

    Xia W-F, Chu Y-M: The Schur convexity of Gini mean values in the sense of harmonic mean. Acta Math. Sci., Ser. B 2011,31(3):1103–1112. 10.1016/S0252-9602(11)60301-9

    MathSciNet  Article  MATH  Google Scholar 

  14. 14.

    Yang Z-H: Schur power convexity of Gini means. Bull. Korean Math. Soc. 2013,50(2):485–498. 10.4134/BKMS.2013.50.2.485

    MathSciNet  Article  MATH  Google Scholar 

  15. 15.

    Alzer H, Janous W: Solution of problem 8. Crux Math. 1987, 13: 173–178.

    Google Scholar 

  16. 16.

    Mao Q-J: Dual means, logarithmic and Heronian dual means of two positive numbers. J. Suzhou Coll. Educ. 1999, 16: 82–85.

    Google Scholar 

  17. 17.

    Janous W: A note on generalized Heronian means. Math. Inequal. Appl. 2001,4(3):369–375.

    MathSciNet  MATH  Google Scholar 

  18. 18.

    Jia G, Cao J: A new upper bound of the logarithmic means. J. Inequal. Pure Appl. Math. 2003.,4(4): Article ID 80

    Google Scholar 

  19. 19.

    Li D-M, Gu Ch, Shi H-N: Schur convexity of the power-type generalization of Heronian means. Math. Pract. Theory 2006,36(9):387–390.

    Google Scholar 

  20. 20.

    Fu L-L, Xi B-Y, Srivastava HM: Schur-convexity of the generalized Heronian means involving two positive numbers. Taiwan. J. Math. 2011,15(6):2721–2731.

    MathSciNet  MATH  Google Scholar 

  21. 21.

    Yang Z-H: Schur power convexity of the Daróczy means. Math. Inequal. Appl. 2013,16(3):751–762.

    MathSciNet  MATH  Google Scholar 

  22. 22.

    Mortici C: Arithmetic mean of values and value at mean of arguments for convex functions. ANZIAM J. 2008,50(1):137–141. 10.1017/S1446181108000199

    MathSciNet  Article  MATH  Google Scholar 

  23. 23.

    Zhang X-M: Geometrically Convex Functions. Anhui University Press, Hefei; 2004.

    Google Scholar 

Download references

Acknowledgements

This research was supported by the Natural Science Foundation of China under Grants 11171307 and 61374086, the Natural Science Foundation of Zhejiang Province under Grant LY13A010004 and the Foundation of Scientific Research Project of Fujian Province Education Department under Grants JK2013051 and JK2012049.

Author information

Affiliations

Authors

Corresponding author

Correspondence to Yu-Ming Chu.

Additional information

Competing interests

The authors declare that they have no conflicts of interest to this work.

Authors’ contributions

All authors contributed equally to the writing of this paper. All authors read and approved the final manuscript.

An erratum to this article is available at http://dx.doi.org/10.1186/1029-242X-2014-516.

Rights and permissions

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Deng, Y., Chu, Y., Wu, S. et al. Schur-geometric convexity of the generalized Gini-Heronian means involving three parameters. J Inequal Appl 2014, 413 (2014). https://doi.org/10.1186/1029-242X-2014-413

Download citation

Keywords

  • generalized Gini-Heronian means
  • Schur-geometric convex
  • Schur-geometric concave
  • parameter
  • inequality